2014
DOI: 10.1371/journal.pbio.1001900
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Mediates Synaptic Scaling Via Synaptic Trafficking of Ca2+-Permeable AMPA Receptors

Abstract: Kim and Ziff examine the molecular mechanism of synaptic scaling, showing that inhibition of neuronal excitability reduces calcium influx into neurons, resulting in decreased calcineurin activity. This leads to increased surface expression of calcium-permeable AMPA receptors as a homeostatic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
160
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(195 citation statements)
references
References 63 publications
(110 reference statements)
13
160
0
Order By: Relevance
“…2D). Because CPARs exhibit a shorter decay time (21)(22)(23), this also indicated the presence of CPARs at KO synapses. We next used 20 μM 1-naphthyl acetyl spermine (naspm), a blocker of CPARs, to determine if CPARs were responsible for an increase of the amplitude in KO neurons ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…2D). Because CPARs exhibit a shorter decay time (21)(22)(23), this also indicated the presence of CPARs at KO synapses. We next used 20 μM 1-naphthyl acetyl spermine (naspm), a blocker of CPARs, to determine if CPARs were responsible for an increase of the amplitude in KO neurons ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…PKA-mediated phosphorylation of GluA1 S845 has been shown to promote plasma membrane insertion of GluA1 and synaptic retention, thereby facilitating LTP (12,(39)(40)(41)(42)(43), whereas dephosphorylation of S845 by CaN and other phosphatases has been correlated with AMPAR endocytosis and LTD (11,12,40,42). In addition, it has been suggested that regulation of GluA1 S845 phosphorylation by PKA and CaN is involved in AMPAR trafficking during bidirectional homeostatic synaptic plasticity in cortical neurons (44,45; but see ref. 46).…”
Section: Discussionmentioning
confidence: 99%
“…A role for GluA1-S845 phosphorylation has also been proposed in the synaptic incorporation of CP-AMPARs during synaptic scaling. Cultures from knock-in mice harbouring the non-phosphorylatable S845A mutation 139 do not undergo TTXinduced synaptic upscaling. Moreover, TTX reduces calcineurin activity and upregulates phosphorylation of GluA1-S845, and inhibition of calcineurin mimics upscaling in the absence of TTX 139 .…”
Section: Ampar Phosphorylationmentioning
confidence: 97%
“…Cultures from knock-in mice harbouring the non-phosphorylatable S845A mutation 139 do not undergo TTXinduced synaptic upscaling. Moreover, TTX reduces calcineurin activity and upregulates phosphorylation of GluA1-S845, and inhibition of calcineurin mimics upscaling in the absence of TTX 139 . Consistent with this, during TTX-induced scaling active PKA is enriched at synapses to mediate phosphorylation of GluA1 S845 and this process also requires the involvement of AKAP150 140 .…”
Section: Ampar Phosphorylationmentioning
confidence: 97%